Tourism environmental impact assessment based on improved AHP and picture fuzzy PROMETHEE II methods - Tian, Chao; Peng, Juan; Zhang, Wen; Zhang, Shuai; Wang, Jian (Technological and Economic Development of Economy, 2020)
With the increasing awareness of environmental protection, the environmental impact assessment (EIA) of tourism attraction problems has attracted extensive attention from all over the world. The purpose of this study is to develop an integrated decision-making method for EIA of tourism attractions in China by using the improved analytic hierarchy process (AHP) method and the extended picture fuzzy preference ranking organization method for enrichment evaluations (PROMETHEE) II method. Herein, picture fuzzy numbers (PFNs) are used to describe decisionmakers’ preference, which can precisely express uncertain and hesitant information in the decisionmaking process. Then the improved AHP method based on expert mean assessment is used to obtain the weights of EIA of tourism attractions, which can reduce the spiteful assessment in the traditional AHP method. Based on the results of the improved AHP method, the picture fuzzy PROMETHEE II method, which can consider the psychological behavior of decision-makers, is applied to assess candidate tourism attractions. Finally, an example of EIA of tourism attractions in China is provided to verify the effectiveness of the developed approach and the credibility of the results. First published online 29 November 2019